Investigating learning skills and use of digital resources by undergraduates in Nigerian universities: a content analysis approach (2023)
This abstract will discuss the learning skills required for the effective use of digital information materials by undergraduate students. In the digital age, students must have the necessary skills to navigate and retrieve information from a wide range of online resources. The purpose of this research is to identify the specific skills that undergraduate students need to develop to effectively utilize digital information materials. The study utilized a mixed-methods approach, including a survey and focus group discussions. The sample consisted of 200 undergraduate students from different disciplines. The findings indicate that students need a range of skills, including information literacy skills, critical thinking skills, technical skills, and digital communication skills. Information literacy skills are crucial for students to be able to locate and evaluate the relevance and credibility of information sources. Critical thinking skills are necessary to analyse and synthesize information from different sources and apply it to specific contexts. Technical skills are essential for students to be able to use the available digital tools and resources effectively. Finally, digital communication skills are necessary for students to communicate their research findings effectively. Based on the findings, it is recommended that institutions of higher learning should develop programs that focus on the development of these skills. These programs should be integrated into the curriculum to ensure that all students have the necessary skills to navigate the digital landscape effectively. Additionally, librarians and academic staff should collaborate to provide support for students in the use of digital information materials. In conclusion, this research highlights the importance of developing the necessary learning skills for the effective use of digital information materials by undergraduate students. With the increasing availability and complexity of digital resources, students must develop the necessary skills to succeed in their academic and professional pursuits.